1991
DOI: 10.1002/1097-0142(19910715)68:2<227::aid-cncr2820680202>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of neuroendocrine carcinomas with combined etoposide and cisplatin. Evidence of major therapeutic activity in the anaplastic variants of these neoplasms

Abstract: Forty-five patients with metastatic neuroendocrine tumors were treated with a regimen of etoposide 130 mg/m2/d for 3 days plus cisplatin 45 mg/m2/d on days 2 and 3. Both drugs were given by continuous intravenous infusion. Among 27 patients with well-differentiated carcinoid tumors or islet cell carcinomas, only two partial objective tumor regressions were observed (7%). Among 18 patients prospectively classified as having anaplastic neuroendocrine carcinomas, however, there were nine partial regressions and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
342
1
17

Year Published

1992
1992
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 751 publications
(369 citation statements)
references
References 3 publications
9
342
1
17
Order By: Relevance
“…For instance, the absence of midgut primaries and male predominance do not mirror classic metastatic low-grade well-differentiated GEP neoplasms in which ileum is the most frequent primary location and sex ratio is around one. This point is even better illustrated by the median OS of our patients, which is higher than the 8-month median OS usually observed in metastatic poorly differentiated NEC (Moertel et al 1991, Mitry et al 1999, Yamazaki et al 2005, Hainsworth et al 2006 but is still lower than expected for metastatic well-differentiated GEP-NEN, for which the 5-year survival is about 50% (Durante et al 2009.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…For instance, the absence of midgut primaries and male predominance do not mirror classic metastatic low-grade well-differentiated GEP neoplasms in which ileum is the most frequent primary location and sex ratio is around one. This point is even better illustrated by the median OS of our patients, which is higher than the 8-month median OS usually observed in metastatic poorly differentiated NEC (Moertel et al 1991, Mitry et al 1999, Yamazaki et al 2005, Hainsworth et al 2006 but is still lower than expected for metastatic well-differentiated GEP-NEN, for which the 5-year survival is about 50% (Durante et al 2009.…”
Section: Discussioncontrasting
confidence: 53%
“…In addition, the differentiation status constitutes a predictive factor of response to cisplatin-based chemotherapy (Mitry et al 1999, Pavel et al 2012. Several studies demonstrated that poorly differentiated NEN respond to cisplatin in more than 50% of cases against !15% for well-differentiated ones (Moertel et al 1991, Mitry et al 1999, Yamazaki et al 2005, Hainsworth et al 2006.…”
mentioning
confidence: 96%
“…Several trials have investigated the effects of chemotherapy, SAAs (either octreotide on lanreotide), and biological response modifiers such as a-interferon in the treatment of these tumours, achieving conflicting results in term of response rate, symptom control, and survival (Kvols et al, 1986;Moertel et al, 1991;Di Bartolomeo et al, 1995;Jensen, 1997;Bajetta et al, 1998Bajetta et al, , 2000Bajetta et al, , 2003Bajetta et al, , 2005Rougier and Ducreux, 1999;Jensen and Doherty, 2001;Mitry and Rougier, 2001;Oberg, 2002;Faiss et al, 2003;Hainsworth et al, 2006), mainly due to the very difficult classification of these tumours and pathological analysis. Although equally able to control hormonal symptoms by reducing the secretion of biological amines and various peptides, these analogues exert a poor tumoricidal effect, being able to decrease tumour size in less than 15% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The first report on EPNEC therapy goes back to 1991 when Moertel and coworkers [68] firstly proposed platinum-etoposide regimens in NEC and identified a 67% response rate with a median survival of 19 months. These apparently excellent results were subsequently confirmed in 41 EPNEC patients who displayed a 42% response rate and a 15-month median survival [69].…”
Section: Issue 1 221 Problem: How To Label These Tumors?mentioning
confidence: 99%